2014
DOI: 10.1364/ao.53.007144
|View full text |Cite
|
Sign up to set email alerts
|

Common-path and compact wavefront diagnosis system based on cross grating lateral shearing interferometer

Abstract: A common-path and compact wavefront diagnosis system for both continuous and transient wavefronts measurement is proposed based on cross grating lateral shearing interferometer (CGLSI). Derived from the basic CGLSI configuration, this system employs an aplanatic lens to convert the wavefront under test into a convergent beam, which makes it possible for CGLSI to test the wavefront of collimated beams. A geometrical optics model for grating pitch determination and a Fresnel diffraction model for order selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The shear ratio β is equal to S/T, where S denotes the shear amount and T represents the beam diameter of the test wavefront in the image plane [32,33]. The bigger shear ratio means the smaller interference region and lower spatial resolution [32].…”
Section: Theoretical Analysis and Simulationmentioning
confidence: 99%
“…The shear ratio β is equal to S/T, where S denotes the shear amount and T represents the beam diameter of the test wavefront in the image plane [32,33]. The bigger shear ratio means the smaller interference region and lower spatial resolution [32].…”
Section: Theoretical Analysis and Simulationmentioning
confidence: 99%
“…Different shear ratios respond to the different measurement accuracy. For example, the common-path cross grating lateral shearing interferometer (CGLSI) was presented in 2014, which is able to suppress the environment vibration and retrieve the wavefront under test [10]. In 2015, Tong Li et al continued their research and demonstrated a QWLSI based on randomly encoded hybrid grating (REHG) [11].…”
Section: Theoretical Analysis 21 Qwlsimentioning
confidence: 99%
“…For example, YONG BUM SEO, et al [13] presented a new method for measuring free-form surfaces based on spatial phase-shifting lateral shearing interferometry, using a birefringence crystal to realize lateral shearing interference, but the optical path construction is more complex, the eight interference fringes were taken in a single exposure process, and the phase is reconstructed by four-step phase-shifting algorithms. For example, Tong Ling, et al [16] proposed a wavefront diagnosis system based on a cross grating lateral shearing interferometer, it has a common path and compact configuration structure and can be used to measure continuous and instantaneous wavefront. The cross grating is the beam displacer component in this system, and the mask lets only ±1 order diffracted light passe through it, to realize the lateral shearing in x-and y-directions.…”
Section: Introductionmentioning
confidence: 99%